Optimization of the Carbonization Parameter of Exhausted Coffee Husk (ECH) as Biochar for Pb and Cu Removal Based on Energy Consumption - Aninda Puari; Rusnam Rusnam; Nika Rahma Yanti (The University of Lampung, 2022)
Recent studies on agricultural waste as a potential precursor of biochar for heavy metals removal from aqueous solution had not considered exhausted coffee husk (ECH) as the potential one. It is well-known that the carbonization process influences the removal performance of biochar, particularly removal efficiency (RE). However, previous studies rarely considered the energy consumption during the carbonization process. The major objective of this study is to investigate the optimum carbonization parameter on ECH biochar for removal of ion Pb and Cu from economic stand point. The ECH biochar was produced at the different heating temperature (300 – 600°C) and heating time (30 – 120 minutes). In regard to specific cost of bio-sorption, the results showed that 500°C was the optimum heating temperature of ECH biochar for the Pb removal, while 600°C was the optimum one for the Cu removal. Furthermore, the heating time experimental outcomes suggested that the optimum heating time were 30 minutes for Pb removal and 120 minutes done Cu removal. Key words: Biochar, carbonization temperature, carbonization time, exhausted coffee husk, specific energy cost